1986
DOI: 10.1063/1.97631
|View full text |Cite
|
Sign up to set email alerts
|

Defect reduction in GaAs grown by molecular beam epitaxy using different superlattice structures

Abstract: Several superlattice structures, grown by molecular beam epitaxy, have been used to reduce the density of threading dislocations originating from the GaAs substrate. Results clearly indicate that compared to epitaxial layers grown directly on GaAs substrates, a GaAs-InxGa1−xAs superlattice (x<0.12) reduces the dislocations by approximately two orders of magnitude. Transmission electron microscopy, electron beam induced current, and etch pit density have been used to characterize the effectiveness of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This presents the onset of the second relaxation process and appears earlier for higher number of MQWs. This relaxation process had been previously observed for highly strained GaAs/InGaAs MQW structures [14]. In the present study the onset of this second relaxation process, "L R ", is different than the critical layer thickness, CLT, and depends on the number of QWs as shown in Fig.…”
Section: Contributedmentioning
confidence: 84%
“…This presents the onset of the second relaxation process and appears earlier for higher number of MQWs. This relaxation process had been previously observed for highly strained GaAs/InGaAs MQW structures [14]. In the present study the onset of this second relaxation process, "L R ", is different than the critical layer thickness, CLT, and depends on the number of QWs as shown in Fig.…”
Section: Contributedmentioning
confidence: 84%
“…Strained-layer superlattices (SLSs) have long been extensively investigated in order to reduce the dislocation density since the 1980s [212][213][214][215]. Matthews et al [212], who proposed the use of an SLS to reduce the TDD, demonstrated that the strain field in GaAsP-GaAs superlattice turned aside the TD propagating upward.…”
Section: Strained-layer Superlattices Defect Filter Layermentioning
confidence: 99%
“…8 4 As/GaAs SLS grown on GaAs substrate. Dislocations are shown by arrows at the SLS/GaAs interfaces [15]. In this case the total thickness of the SLS exceeds the critical thickness for the genierationls of imisfit dislocations for bulk grown Ino.…”
Section: Current Limitations In Binary-ternary Strained Layer Supmentioning
confidence: 99%
“…The potential of ALIE tin -,io\ with a highl ilegrec ()I H Abstract-Successful long-term room-lemperature operation of average lattice constant can be matched to that of GaAs lnGaAs/GaAsP slrained-layer superlaltice (SIS) light-cmilling diodes Therefore this SI S can be incorporated with GaAs and , defect reduction (15]. ma(ched to that of (he substrate is stable tinder high-leV; current and solar cell [16] have been reported.…”
Section: Inas and Lngaasmentioning
confidence: 99%